Constructing a Travel Landscape: A Case Study of the Sljeme Motels along the Adriatic Highway. Issue 1 (15th February 2018) - Čavlović, Melita
Abstract : The construction of the Adriatic Highway began in 1954, the result of the belated modernisation of the Federal People's Republic of Croatia. The aim was to develop a unique transportation system and by doing so, to help create a cohesive territory from previously disconnected fragments of coastline. It was not until the 1960s, thanks to the state's increasing interest in tourism, that traffic increased dramatically. The Sljeme motel chain along the new highway, designed by architect Ivan Vitić in 1965, is emblematic of architecture developed primarily for travellers in cars.1 These motels could even be perceived as extensions of the highway, a tourist architecture that differs from the subsequent period when tourist complexes were built en masse along the coast and designed exclusively as final travel destinations.